2007
DOI: 10.2215/cjn.00230107
|View full text |Cite
|
Sign up to set email alerts
|

Presenting Features and Short-Term Outcome According to Pathologic Variant in Childhood Primary Focal Segmental Glomerulosclerosis

Abstract: Background: This was a retrospective analysis of children in one center who had primary (idiopathic) FSGS. Design, setting, participants, and measurements: There were 41 patients: 34.1% female, 65.9% male, 80.5% black, and 19.5% white. At presentation, the mean age was 10.9 ؎ 0.9 yr. The mean time of follow-up was 3.9 ؎ 0.5 yr.Results: During the observation period, the systolic BP (SBP) and diastolic BP (DBP) remained stable, serum albumin rose slightly, and the GFR was stable. Among those who received cortic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 32 publications
2
33
1
Order By: Relevance
“…Collapsing FSGS has been described by many authors from different parts of the world as a cause of SRNS in children [9,12,13,14]. Our patient had high blood pressure at presentation, and this is similar to previous reports of initial high blood pressure in affected children [13].…”
Section: Discussionsupporting
confidence: 87%
“…Collapsing FSGS has been described by many authors from different parts of the world as a cause of SRNS in children [9,12,13,14]. Our patient had high blood pressure at presentation, and this is similar to previous reports of initial high blood pressure in affected children [13].…”
Section: Discussionsupporting
confidence: 87%
“…The latter might be considered to include familial/genetic forms, virus-associated forms, drug-induced forms, and forms mediated by adaptive structural-functional responses (i.e., in the setting of congenital or acquired reduction of renal mass/nephron complement). Clinical response and prognosis may relate to the histologic variant, most notably the glucocorticioid responsiveness of the tip lesion and the aggressive, unrelenting nature of the collapsing variants (21,22). It is with this in mind that the variants are included in standard pathology reports.…”
Section: Classificationmentioning
confidence: 99%
“…The FSGS-CT findings support significant differences in demographic features between histologic subtypes. Tip and collapsing variants were more common in teenagers and adults than children (5,6,12,(14)(15)(16)(17)(18)(19). Only 29% of tip patients were children aged 2-12 years at onset of FSGS, whereas 43% were over 18 years.…”
Section: Discussionmentioning
confidence: 99%
“…These variants include the common generic NOS type, the aggressive collapsing type, the abruptly presenting tip type, the early-stage cellular type, and the perihilar type common in secondary adaptive FSGS (13)(14)(15)(16)(17). Several retrospective series have suggested that FSGS histologic subtypes vary in incidence and correlate with remission status and outcome.…”
Section: Discussionmentioning
confidence: 99%